Spatio-Temporal Analysis of Land Use Land Cover Changes and Spectral Normalized Difference Indices in Multan City, Pakistan - Muhammad Hashim,; Atta-Ur-Rahman,; Basit Nadeem,; Faisal Aziz,; Muhammad Dawood,; Muhammad Qasim,; Muhammad Umar Farooq,; Shazia Muneer, (Al-Qanṭara, 2024)
The present study focuses the change in land use land cover along with the spectral normalized indices in Multan city for last three decades 1993 to 2023. The study years are 1993, 2003, 2013 and 2023. The land use land cover changes are evaluated through four specified classes including built-up area, agricultural land, barren land and water bodies while the spectral indices are NDVI, NDBI, NDBaI and NDWI. Urbanization dynamics requires quantitative descriptions and spatial distributions of urban areas, particularly in the face of rapid urban land-cover changes. To validate the method's accuracy, it was compared against ground truth data obtained from Landsat 5, Landsat 7, Landsat 8, and Landsat 9 images. The results of the accuracy assessments demonstrated the effectiveness of the method, with Overall Accuracy (OA) ranging from 0.854 to 0.913 and Kappa values ranging from 0.699 to 0.722. These findings affirm that the spectral normalized difference approaches can accurately describe spatial distributions and provide detailed information about urban extents. The findings showed considerable changes in all the four classes especially in built-up areas and agricultural areas. The built-up area increased in each study year along with decrease in agricultural land.